Implementación de la metodología SMED en los cambios de producto de las máquinas de empaque de una empresa de alimentos de Roldanillo (2021)
The SMED methodology for the application of our project is fundamentally based on its main objective, which consists of the significant decrease in the times of the factory's product changes, since these improvements will increase the amount of good production and decrease the idle time in the packaging lines, contributing directly to the reduction of planned stoppages. Within this methodology, five phases are established, in which the operations that take place in the product change are analyzed and evaluated and thus find new work proposals and make it possible to increase the performance of the lines.